Human Person of Human Resource - Education in the Neo-Liberal Era - Roxana CĂPUŞAN (Revista Transilvană de Ştiinţe Administrative, 2003)
The current trend in education, as in almost all fields of life, is towards an aggressive corporatism which poses as globalization, while trying to apply economic principles to all aspects of life. In the case of education, such an approach is extremely damaging, because it affects the way human beings themselves are seen- as mere resources. This path will lead to a severe depersonalization of society and to new and aggressive social divisions. True globalization (an internationalism which encompasses more than just the economic aspects) is the only valid solution.